Integrated sample‐pretreatment strategy for separation and enrichment of microplastics and primary aromatic amines in the migration of teabag. Issue 4 (28th December 2021) - Ouyang, Xiaoyan; Hu, Yuling; Li, Gongke
Abstract: In this work, an integrated sample‐pretreatment strategy for the separation and enrichment of microplastics and primary aromatic amines from the migration of teabag was developed. The migration solution of teabag was passed through a homemade device. The microplastics were firstly captured by a silver membrane, and then the primary aromatic amines were enriched by a solid‐phase extraction column. The microplastics migrated from teabag were detected by attenuated total reflection‐Fourier transform infrared spectrometer and Raman spectroscopy. The data showed the character, the number of particles, area ratio, and morphology of microplastics migrated from the teabag. Subsequently, after the enrichment procedure, a sensitive analytical method for primary aromatic amines was established followed by ultra‐high performance liquid chromatography‐tandem mass spectrometry. The method showed wide linear ranges with R 2 greater than 0.9915, low limits of detection (2–18 ng/L), and low limits of quantification (8–50 ng/L). The developed method was adopted to analyze microplastics and primary aromatic amines migrated from nylon and polyethylene terephthalate teabag under different temperatures and times. The integrated sample‐pretreatment strategy displayed promising potentials in the one‐step preparation of the microplastics and hazardous molecules in the sample of environment and food security.